2014
DOI: 10.1007/s00439-014-1512-7
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing-based molecular diagnosis of 82 retinitis pigmentosa probands from Northern Ireland

Abstract: Retinitis pigmentosa (RP) is a group of inherited retinal disorders characterized by progressive photoreceptor degeneration. An accurate molecular diagnosis is essential for disease characterization and clinical prognoses. A retinal capture panel that enriches 186 known retinal disease genes, including 55 known RP genes, was developed. Targeted next-generation sequencing was performed for a cohort of 82 unrelated RP cases from Northern Ireland, including 46 simplex cases and 36 familial cases. Disease-causing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 78 publications
6
55
1
1
Order By: Relevance
“…These variants account or likely account for the clinical diagnosis of IRD in 51% of the 537 individuals referred for diagnostic testing, including 208 autosomal-recessive, 50 autosomal-dominant and 13 X-linked recessive cases. Other studies employing NGS have shown higher molecular diagnostic rates than reported in this study, including Eisenberger and colleagues,21 Zhao and colleagues22 and the Saudi Mendeliome group 23. We attribute differences in diagnostic success rates to a number of factors.…”
Section: Discussionmentioning
confidence: 41%
“…These variants account or likely account for the clinical diagnosis of IRD in 51% of the 537 individuals referred for diagnostic testing, including 208 autosomal-recessive, 50 autosomal-dominant and 13 X-linked recessive cases. Other studies employing NGS have shown higher molecular diagnostic rates than reported in this study, including Eisenberger and colleagues,21 Zhao and colleagues22 and the Saudi Mendeliome group 23. We attribute differences in diagnostic success rates to a number of factors.…”
Section: Discussionmentioning
confidence: 41%
“…In order to increase mutation detection rate, a large number of genes must be sequenced. NGS testing of several retinal dystrophy patient cohorts have been reported recently, with published mutation detection rates for nonsyndromic retinal dystrophy of 37 [13 && ], 51 [12 & ], 55 [14], 60 [15], and 70% [16], using targeted enrichment NGS panel tests.…”
Section: Mutation Detection Ratementioning
confidence: 99%
“…Of note, light sensitivity may be one major symptom in patients with variants in CACNA1F , CABP4 , and CACNA2D4 in addition to phenotypic variability sometimes leading to more progressive IRD and thus the term icCSNB may be misleading (reviewed in Zeitz et al, ). More than 150 different variants in CACNA1F and only a few in CABP4 and CACNA2D4 lead to icCSNB or similar phenotypes (reviewed and summarized in 2015 in Zeitz et al, ; additional publications since then, Ba‐Abbad et al, ; Hove et al, ; X. F. Huang et al, ; L. Huang et al, ; Patel et al, ; Sun et al, ; Xu et al, ; Zhao et al, ; Q. Zhou et al, ). The pathogenic variant spectrum comprises missense, nonsense, and splice‐site variants, small insertions and deletions, gross deletions, and complex rearrangements with most of the variants representing missense or nonsense variants (HGMD_Pro; Stenson et al, ; Zeitz et al, ).…”
Section: Introductionmentioning
confidence: 99%